The Short and Long Term Performance Persistence in the Central European Banking Industry - Krzysztof Jackowicz; Oskar Kowalewski; Łukasz Kozłowski (Contemporary Economics)
This article investigates the scale of performance persistence in the Central European banking industry. Contrary to the existing literature, we test not only for the short-term performance persistence but we propose also a novel method of analyzing the long-term persistence. Using an extensive dataset, covering the 1992-2009 period, we establish that banks’ results are strongly persistent in two-years sub-periods as well as in the long-run. Moreover, we find that the strength of studied phenomenon is not significantly influenced by the macroeconomic environment, banks size and capital base and country-specific factors.